S‐Block Multiple Bonds: Isolation of a Beryllium Imido Complex. Issue 17 (10th March 2021) - Wang, Guocang; Walley, Jacob E.; Dickie, Diane A.; Molino, Andrew; Wilson, David J. D.; Gilliard, Robert J.
Abstract: A common feature of d ‐ and p ‐block elements is that they participate in multiple bonding. In contrast, the synthesis of compounds containing homo‐ or hetero‐nuclear multiple bonds involving s‐block elements is extremely rare. Herein, we report the synthesis, molecular structure, and computational analysis of a beryllium imido (Be=N) complex (2 ), which was prepared via oxidation of a molecular Be 0 precursor (1 ) with trimethylsilyl azide Me3 SiN3 (TMS‐N3 ). Notably, compound 2 features the shortest known Be=N bond (1.464 Å) to date. This represents the first compound with an s‐block metal‐nitrogen multiple bond. All compounds were characterized experimentally with multi‐nuclear NMR spectroscopy ( 1 H, 13 C, 9 Be) and single‐crystal X‐ray diffraction studies. The bonding situation was analyzed with density functional theory (DFT) calculations, which supports the existence of π‐bonding between beryllium and nitrogen. Abstract : The first s‐block metal‐nitrogen double bond is synthesized! The shortest beryllium‐nitrogen bond has been prepared via oxidation of Be 0 .